Measuring personality congruency effects on consumer brand intentions in celebrity-endorsed brands. Issue 3 (8th February 2021) - Arora, Nilesh; Prashar, Sanjeev; Tata, Sai Vijay; Parsad, Chandan
Abstract : Purpose: Brand managers frequently use well-known celebrities to position their brands and capture consumers' attention to improve the brand's market share. The attachment of a celebrity with a brand creates a human image for a brand and helps in personifying its image. The consumer perceives the brand as an individual and relates his personality, as well as the personality of the celebrity with that of the brand. It becomes pertinent for marketers to understand how brand-celebrity personality congruence and brand-consumer personality congruence affect the brand reputation, uniqueness and purchase intentions. Thus, the purpose of this study is to understand the relationship between the two personality congruence aspects – brand & celebrity personalities and brand & consumer personalities, and their impact on the reputation of the brand and its uniqueness. Further, the paper aims to examine the impact of the brand reputation and brand uniqueness on purchase intentions. Design/methodology/approach: The present study uses Aaker's five-factor personality scale to study the personality congruence effects on brand reputation, brand uniqueness and purchase intentions. The literature review was carried out to categorize factors related to celebrity personality, brand personality and consumer personality. The data for this study was collected through questionnaires from 1, 235 respondents. In the first step, congruencies between celebrity, brand and consumer personality were determined. This was followed by a two-stage structural equation modelling for assessing the model fit and testing the hypotheses. Findings: From the study results, it is observed that brand-celebrity congruency influences brand reputation and brand uniqueness. However, brand-consumer congruency had an effect only on brand reputation and not on brand uniqueness. Both brand reputation and uniqueness have favourable impact on consumers purchase intentions. Originality/value: This study contributes to the existing literature on celebrity endorsement by extending the discussion with personality-based congruence. The research deciphered two aspects of identification, i.e. consumer-brand personality congruence and brand-celebrity congruence. The paper hypothesized the favourable association between brand personality and consumer personality congruence and brand uniqueness. However, it was observed that brand personality-consumer personality identification had an insignificant influence on brand uniqueness. This is contrary to the findings of some studies in the literature. Further investigation of this relationship in the future may add a new dimension to the identification context.